Different Arthropod Pests of Cashew with Special Reference to Red Banded Thrips (Selenothrips rubrocinctus giard)-A Review - Sthitapragyan, Soumya; Mukherjee, S. K. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Cashew yield is highly influenced by adopting scientific management practices. However the crop suffers from biotic and abiotic stress situations for which the cashew yield is drastically affected if not attended in time. Earlier many workers have done intensive studies on the influence of environmental factors on crop physiology and yield of this crop. The crop is also reported to be attacked by a number of insect pests as well as microbial pathogens causing diseases. About 400 species of arthropods are known to infest cashew till now (Technical Bulletin, DCR, 2015) while 70 species of insect pests have been reported to infest cashew in different stages of crop growth in India (Pillai et al .,1979). Among these several insect pests cashew stem and root borer is the most important pest of this region followed by the incidence of Tea Mosquito Bug. Besides this Shoot Tip Caterpillar, Leaf Miner, Leaf and Blossom Webber, Apple and Nut Borer and Thrips also cause yield reduction in unmanaged plantations. I reviewed 1) The various arthropod pests of Cashew 2) Different species of thrips infesting cashew 3) Red banded thrips of Cashew and their morphology , seasonal incidence and biology 4) Damage and control of Red Banded Thrips of Cashew. It is recommended that minimizing the pesticides applications and adopting different IPM practices against insects and pests, larger consideration should be given to farmer and their educational formats. The present article will shed light on the efficacy of various insecticides for the control of a highly devastating and emerging pest Red Banded Thrips in Cashew.
Keywords: Cashew; foliage thrips; Bioefficacy; Selonothrips rubrocinctus Giard